The Use of Landsat Image and Census Data for Modelling Population Density and Urban Density in Palembang, Indonesia - Muhammad Fajri Romdhoni (Departement of Architecture, Universitas Islam Indonesia, 2020)
This research is to understand the condition of population Density concentration in the city of Palembang. According to the 2018 United nations booklet (United Nations, 2018), Palembang's city is dimmed to be one of the fastest-growing cities in Indonesia. Palembang has an annual growth rate between 2.4% to 6%, and according to the research, the exponential growth will impact its urban fabric conditions. The researcher's problem in urban growth is the limitation of datasets available from the government, and mostly the datasets are not tailored for urban designers need. The statistical datasets available are often linked to the administrative area called